Comparison of Injection Meglumine Antimoniate with a Combination of Injection Meglumine Antimoniate and Carbon Dioxide Fractional Ablative Laser in Treatment of Cutaneous Leshmaniasis - Ismat Jabin, Azhar Hosain Minhas, Farrah Yousaf, Hina Syeda, Samra Irum, Shamaila Rafique, Ghazala Yasmeen, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To see the efficacy of meglumine antimoniate alone in comparison with combination of meglumine antimoniate and CO2 ablative laser among patients with cutaneous leishmaniasis. Study design: Quasi-experimental study. Place and duration of study: Department of Dermatology, Pakistan Emirates Military Hospital, Rawalpindi from 9th July 2020 to 8th January 2021. Methodology: Sixty patients (30 in each group) diagnosed cases of cutaneous leishmaniasis by skin biopsy or slit skin smear were enrolled. In group A; intramuscular injection of meglumine antimoniate (dose 20 mg/kg daily) was administered for 28 days and group B was treated with intramuscular meglumine antimoniate injection along with fractional C02 ablative laser. Standard digital photography was done before start of treatment and then every 2 weeks. Results: Efficacy of meglumine antimoniate alone was observed in 60% of patients while it was 86.7% when combined with fractional CO2 ablative laser. Better outcome was observed when such patients were treated with both meglumine antimoniate and fractional CO2 laser. Efficacy was measured after 6 x weeks in all patients of both groups. Clinical Implication: Hence CO2 lasers are latest modality of treatment with minimal side effects and can be used in treatment of patients with cutaneous leishmaniasis. Conclusion: Efficacy of meglumine antimoniate plus fractional CO2 laser found to be higher as compared to meglumine antimonate alone in treating cutaneous leishmaniasis. Keywords: Cutaneous leishmaniasis, CO2 fractional ablative laser, Meglumine antimoniate, Slit skin smear